Anti-fog liquid crystal lens with color changing and shading functions

By setting a dye liquid crystal color change layer between the lens substrates and an anti-fog layer on the inner side, and using the conductive layer to control color changes, the existing lenses cannot discolor and block light and lack of anti-fog in an environment with insufficient light, achieving convenient light shading control and clear field of view.

CN119620476APending Publication Date: 2025-03-14DONGGUAN JUGAO OPTOELECTRONICS TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411957372.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing color-changing lenses cannot achieve color-changing shading in environments with insufficient light, and lack anti-fog function, which affects use.

Method used

An anti-fog liquid crystal lens with color distortion shading was designed. By setting a dye liquid crystal color distortion layer between the two lens substrates and an anti-fog layer is set on the inside of the lens. The conductive layer is used to control the color change of the dye liquid crystal color distortion layer to achieve a light shielding effect while reducing fog adhesion.

Benefits of technology

It realizes switching between light transmission and shading in any light environment, which is easy to use, while avoiding fog shading, ensuring a clear field of view, and improving the intensity and light transmittance of the lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119620476A_ABST
    Figure CN119620476A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lenses, and discloses an antifogging liquid crystal lens with color changing and shading functions, which comprises a color changing base layer, the color changing base layer is composed of two layers of lens base materials and a dye liquid crystal color changing layer positioned between the two layers of lens base materials, and a conductive layer is arranged on one side, close to the dye liquid crystal color changing layer, of each lens base material. First adhesive glue is arranged on the upper surface and the bottom surface of the color-changing base layer, and a hardening layer is arranged on the first adhesive glue on the upper layer; the dye liquid crystal color-changing layer is arranged between the two lens base materials, the dye liquid crystal color-changing layer is electrified to change the color from a transparent color to a colorful color, the shading effect is realized, light transmission and shading can be switched anytime and anywhere, and the lens is convenient to use; meanwhile, the anti-fog layer is arranged on the inner side of the lens, so that attachment of water mist is reduced, and mist shielding in a cold environment is avoided; and the hardening layer and the optical coating film are arranged on the front side of the lens, so that the strength of the lens is improved, the light transmission of the lens is ensured, and the shading lens can be used in various fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lenses, in particular to an anti-fog liquid crystal lens with color-changing and light-shielding functions. Background Art

[0002] Translucent lenses are used in glasses, windows and other scenes to provide light transmission and shielding. With the continuous development of modern technology, people's functional requirements for eyeglass lenses are also increasing. Traditional eyeglass lenses mainly meet basic vision correction needs, while modern lenses begin to integrate a variety of high-tech elements to provide users with a more comfortable, convenient and diverse visual experience. Among them, color change, light blocking, anti-fog and other functions have become hot spots in the development of eyeglass lens technology in recent years.

[0003] Photochromic lenses can automatically adjust the color of the lenses according to the intensity of external light, effectively protecting the eyes from strong light stimulation, while maintaining sufficient light transmittance in low-light environments to ensure visual clarity. However, traditional photochromic lenses mostly use chemical photochromic materials, which have limited color-changing effects and response speeds, and long-term use may cause material aging, affecting lens performance; existing photochromic glasses can only achieve lens color change in an environment with sufficient light, and cannot meet the needs of daily color change and shading in an environment with poor lighting; and the inner side of the lens lacks anti-fog function, and is prone to fogging in cold weather, affecting use. Therefore, an anti-fog liquid crystal lens with color change and shading is proposed. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides an anti-fog liquid crystal lens with color-changing and light-shielding functions to solve the problems of the background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: an anti-fog liquid crystal lens with color-changing and light-shielding function, comprising a color-changing base layer, the color-changing base layer is composed of two layers of lens substrates and a dye liquid crystal color-changing layer located between the two layers of lens substrates, a conductive layer is provided on one side of the lens substrate close to the dye liquid crystal color-changing layer, a first adhesive is provided on the upper surface and the bottom surface of the color-changing base layer, a hardening layer is provided on the first adhesive located on the upper layer, an optical coating is provided on the upper surface of the hardening layer, an anti-fog layer is provided on the bottom surface of the first adhesive located on the lower layer, a protective film is provided on the bottom surface of the anti-fog layer and the upper surface of the optical coating, and an FPCB control circuit for controlling the change of the dye liquid crystal color-changing layer through the conductive layer is installed on the outer wall of the lens substrate located on the upper layer.

[0006] Preferably, the number of the color-changing base layers is one or more layers. When the color-changing base layers are multiple layers, two layers of first adhesive are respectively arranged on the two end surfaces of the multiple color-changing base layers, and a second adhesive is arranged between adjacent color-changing base layers, and the colors of the dye liquid crystal color-changing layers in the multiple color-changing base layers are different.

[0007] Preferably, the materials of the first adhesive and the second adhesive are preferably OCA optical adhesive.

[0008] Preferably, the material of the hardened layer is TAC or PC.

[0009] According to the anti-fog liquid crystal lens with color-changing and light-shielding function as claimed in claim 1, the material of the anti-fog layer is preferably CAP or TAC.

[0010] Preferably, the material of the lens substrate is PC or PET.

[0011] Preferably, a sealing line is provided at the edge between the two lens substrates, and the sealing line is used to seal the dye liquid crystal color-changing layer between the two lens substrates.

[0012] Preferably, the sealing line comprises an inner sealing line and an outer sealing line, and the dye liquid crystal color-changing layer is located in the area divided by the inner sealing line.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The present invention arranges a dye liquid crystal color-changing layer between two lens substrates, and changes its color from transparent to colorful by energizing it, thereby achieving a shading effect. The light-transmitting and light-shielding states can be switched anytime and anywhere, which is convenient for use. At the same time, an anti-fog layer is arranged on the inner side of the lens to reduce the adhesion of water mist, thereby avoiding fog obstruction in cold weather. A hardening layer and an optical coating are also arranged on the front side of the lens, which not only improves the strength of the lens, but also ensures the light transmittance of the lens, thereby meeting the use of shading lenses in various fields.

[0015] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of the distribution of the dye liquid crystal color-changing layer of the lens of the present invention;

[0017] Figure 2 It is a schematic diagram of the cross-sectional structure of a single-layer color-changing base layer of the present invention;

[0018] Figure 3 It is a schematic diagram of the cross-sectional structure of the multi-layer color-changing base layer of the present invention;

[0019] Figure 4 This is a schematic diagram of the structure of the sealing line of the present invention sealing the dye liquid crystal color-changing layer.

[0020] In the figure: 1. color-changing base layer; 11. lens substrate; 12. dye liquid crystal color-changing layer; 13. conductive layer; 2. sealing line; 21. external sealing line; 22. internal sealing line; 3. first adhesive; 4. anti-fog layer; 5. protective film; 6. hardening layer; 7. optical coating; 8. second adhesive; 9. FPCB control circuit. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this technical field without creative work are within the scope of protection of the present invention.

[0022] Please refer to the figure, the present invention provides an anti-fog liquid crystal lens with color changing and shading, which is intended to achieve color changing and shading, anti-fogging of the lens, improve the strength of the lens, and protect the lens.

[0023] Embodiment 1:

[0024] This example uses a single-layer color-changing base layer 1, such as Figure 2 The anti-fog liquid crystal lens with color-changing and light-shielding properties is prepared as shown;

[0025] Preparation of color-changing base layer 1:

[0026] The lens substrate 11 is made of PC or PET material and cut into a desired shape. A conductive layer 13 is formed on the lens substrate 11 by depositing, for example, conductive polymers, conductive metals, conductive nanowires or metal oxides such as ITO (Indium Tin Oxide);

[0027] An internal sealing line 22 is drawn on one of the lens substrates 11 by using the nozzle of the spraying equipment, and an external sealing line 21 is drawn outside the internal sealing line 22 by using another nozzle; the spraying equipment can have two nozzles at the same time to spray the internal sealing line 22 and the external sealing line 21 simultaneously, which can include the step of forming the sealing line 2.

[0028] According to this embodiment, when selecting suitable seals as the above-mentioned internal seals and external seals and the formation stage of internal sealing lines and external sealing lines, the uniformity of the sealing lines is determined through process optimization; for example, the thickness deviation, line width deviation and straightness deviation can be improved.

[0029] In one example, the viscosity of the inner seal line 22 can be higher than the viscosity of the outer seal line 21. When the viscosity of the inner seal line 22 is higher, its diffusivity is lower, and a uniform seal line can be formed when the two lens substrates 11 are closed. On the other hand, when the viscosity of the inner seal line 22 is lower, its diffusivity will increase, affecting the uniformity of the seal line 2. When the outer seal line 21 is, its ductility is better, which may be beneficial to reduce the difference in height between the seal line area and the active area.

[0030] The viscosity of the inner sealing line 22 can be in the range of 100 or 100 or 300 or 100 or 100 mPas. Specifically, the viscosity of the inner sealing line 22 is 110,00 mPas or higher, 120,00 mPas or higher, more than 130 mPas, more than 140,00 mPas, 150,00 mPas or higher, 160,00 mPas or higher, 170,00 mPas or higher, more than 180,00 mPas, it can be 190 or 00 mPas or higher, and it can also be 200 or 00 mPas or higher. 00mPas or less, 300,00mPas or less, 290,00mPas or less, 280,00mPas or less, can be 270,00mPas or less, 260,00mPas or less, 250,00mPas or less, 240,00mPas or less, 230,00mPas or less, 220,00mPas or less or 210,00mPas or less. According to a specific embodiment of the present application, the viscosity of the inner sealing line 22 can be in the range of 190,000mPas to 210,000mPas.

[0031] The viscosity of the above-mentioned external sealing line 21 is specifically: below 59,00mPas; 58.00mPas or lower, 57,00mPas or lower, 56,00mPas or lower, 55,00mPas or lower, 54,00mPas or lower, it can be 53 or 00mPas or 52 or 00mPas, it can be 20,00mPas or higher, 25,00mPas or higher, 30,00mPas or higher, 35,00mPas or higher, 40,00mPas or higher, 45,00mPas or higher, 50,00mPas or higher. According to a specific embodiment of the present application, the viscosity of the external sealing line 21 can be in the range of 51,000 mPas to 53,000 mPas, and the viscosity of the external silane can be lower than, for example, 60,000 mPas. When the viscosity of the external silane is too high, its diffusivity is low, which may cause a greater degree of unevenness in the thickness of the sealing line after closing. Therefore, the viscosity of the external silane should be within the above range.

[0032] Select appropriate materials as the materials of the inner sealing line 22 and the outer sealing line 21, and control the discharge amount and drawing speed of the nozzle of the spraying equipment;

[0033] Dye liquid crystal color-changing layer 12: The dye liquid crystal color-changing layer 12, as a layer containing at least a liquid crystal compound, may refer to a liquid crystal layer that controls the back state of the above-mentioned liquid crystal compound by external signal heat or the like. However, the application of the dye liquid crystal color-changing layer 12 is an example of the present application; if necessary, other transparent variable layers of other spaces may also be used, such as an electrochromic material layer, a photochromic material layer, an electrophoretic material layer, or a dispersed particle back layer or the like. In an embodiment, the scope of the dye liquid crystal color-changing layer 12 includes: a layered pattern containing liquid crystal compounds whose back direction can be controlled by external signal recognition or the like. Any type of liquid crystal compound can be used for the liquid crystal compound, as long as its back direction can be changed by the recognition of an external signal. For example, the liquid crystal compound has a smectic liquid crystal compound, and a (nematic) liquid crystal compound or a cholesterol (cholesteric) liquid crystal compound or the like can be used. In addition, in order to enable its back direction to change due to the recognition of an external signal, the liquid crystal compound may be, for example, a compound that does not have a polymerizable morphological group or a bridging morphological group.

[0034] The dye liquid crystal color-changing layer 12 can be formed before or after the two lens substrates 11 are closed. In one example, if the step of forming the dye liquid crystal color-changing layer 12 is completed before closing, the dye liquid crystal color-changing layer 12 can be formed by applying the dye liquid crystal color-changing material in the area divided by the internal sealing line 22 using, for example, an ODF (One Drop Filling) process. In another example, if the step of forming the dye liquid crystal color-changing layer 12 is performed after closing, the dye liquid crystal color-changing is achieved through a process of injecting the dye liquid crystal color-changing material into the area divided by the internal sealing line 22 through certain areas of the internal sealing line 22 and the external sealing line 21.

[0035] After the two lens substrates 11 are closed, the sealing strip can be hardened by, for example, thermal curing and / or ultraviolet irradiation, so as to produce the color-changing base layer 1.

[0036] An FPCB control circuit 9 connected to the conductive layer 13 is installed on the side wall of the lens substrate 11 facing outward. The FPCB control circuit 9 controls the dye liquid crystal color-changing layer 12 to be energized through the conductive layer 13, thereby achieving color change and shading control. The FPCB control circuit 9 cuts off the power to the dye liquid crystal color-changing layer 12, and the dye liquid crystal color-changing layer 12 is in a colorless state.

[0037] The shading control method may include physical button control, physical touch control, gesture recognition control, voice recognition control, mobile phone Bluetooth APP control, light sensor control, etc., which may be determined based on the actual application scenario and actual application product.

[0038] The power supply method may include button batteries, solar cells, rechargeable lithium batteries, etc., which are determined based on the actual application scenario and actual application products.

[0039] Embodiment 2:

[0040] This example uses a multi-layer color-changing base layer 1, such as Figure 3 The anti-fog liquid crystal lens with color-changing and light-shielding properties is prepared as shown;

[0041] The color-changing base layer 1 is prepared based on the steps described in Example 1, and a color-changing base layer 1 having more than one layer is selected. A second adhesive 8 is applied between the multiple color-changing base layers 1. The second adhesive 8 is preferably an OCA optical adhesive with light transmittance. The second adhesive 8 is cured by ultraviolet or heat curing, and then the multiple color-changing base layers 1 are compounded together to form a multi-layer color-changing base layer 1.

[0042] For example, two layers of color-changing base layers 1 of different colors are used, one of which is layer a and the other is layer b;

[0043] The power of layer a and layer b is turned off to be transparent;

[0044] Power on layer a (power off layer b), and layer a changes color;

[0045] Power on layer b (power off layer a), and layer b changes color;

[0046] Power on layer a and layer b at the same time, and they change color at the same time;

[0047] By laminating the lenses in multiple layers according to this structure, a variety of colors can be changed.

[0048] Embodiment three:

[0049] On the basis of the first and second embodiments, when the color-changing base layer 1 is a single layer, the first adhesive 3 is applied on both sides thereof, and when the color-changing base layer 2 is a multi-layer, the first adhesive 3 is also applied on both end surfaces of the multi-layer color-changing base layer 2, and the first adhesive 3 is preferably an OCA optical adhesive;

[0050] An anti-fog layer 4 is coated on the first adhesive 3 located at the lower layer, and the first adhesive 3 is cured by ultraviolet or heat curing. The anti-fog layer 4 is preferably made of CAP or TAC material;

[0051] CAP is a polymer in which the hydroxyl groups in the cellulose molecules are esterified with propionate; it has long side chains, low water absorption, and excellent physical and mechanical properties. CAP material has good dimensional stability, weather resistance, moisture resistance, cold resistance, softness, transparency, smooth surface, good gloss, and electrical insulation.

[0052] TAC has high transparency, low optical distortion, good chemical corrosion resistance and certain flexibility; these characteristics make TAC perform well in the optical field and is often used to manufacture eyeglass lenses and camera lenses to provide clear visual effects;

[0053] CAP or TAC as the inner side of the lens can prevent fogging and maintain a clear field of vision.

[0054] A hardening layer 6 is coated on the first adhesive 3 located on the upper layer, and the first adhesive 3 is cured by ultraviolet or thermal curing. The hardening layer 6 is preferably made of TAC or PC material; PC has high transparency, high impact strength, good electrical insulation and heat resistance; using TAC or PC material as the hardening layer 6 on the outside of the lens can effectively improve the hardness of the lens.

[0055] Embodiment 4:

[0056] On the basis of the third embodiment, a layer of optical coating 7 is coated on the upper surface of the hardened layer 6 to improve the anti-reflection and light transmittance of the lens, and also to be waterproof and oil-proof.

[0057] Optical coating 7 is prepared by selecting PET resin material;

[0058] PET resins generally refer to resins in which 80% or more of the repeating units are terephthalate, and may also contain other dicarboxylic acid components and diol components. Although not particularly limited, other dicarboxylic acid components include isophthalic acid, p-β-hydroxybenzoylformate, 4,4′-dicarboxydiphenyl, 4,4′-dicarboxybenzophenone, bis(4-carboxyphenyl)ethane, adipic acid, triproic acid and / or 1,4-dicarboxycyclohexane.

[0059] As for other diol components, although not particularly limited, they may be propylene glycol, butylene glycol, neopentyl alcohol, diethylene glycol, cyclohexanediol, ethylene hydroxyl additions of bisphenol A, polyethylene glycol, polypropylene glycol and / or polytetramethylene glycol, etc.

[0060] The above-mentioned dicarboxylic acid components or diol components can be used in combination of two or more as required. In addition, hydroxycarboxylic acids such as p-hydroxybenzoic acid can also be used in combination. In addition, as other copolymerization components, dicarboxylic acid components or diol components containing a small amount of amide bonds, carbamate bonds, ether bonds and carbonate bonds can also be used.

[0061] As a method for preparing PET-based resins, there are methods of directly re-condensing terephthalic acid, ethylene glycol and / or other dicarboxylic acids or other diols as needed; methods of re-condensing dialkyl esters of terephthalic acid and ethylene glycol and / or dialkyl esters of other dicarboxylic acids or other diols after ester exchange reaction; and methods of re-condensing ethylene glycol esters of other dicarboxylic acids and / or other diol esters as needed using terephthalic acid and / or other dicarboxylic acids as needed.

[0062] In each polymerization reaction, a polymerization catalyst containing an antimony-based, titanium-based, germanium-based, or aluminum-based compound, or a polymerization catalyst containing a phase-based composite compound may be used.

[0063] The polymerization reaction conditions are: the monomers used; the catalyst, which can be appropriately selected according to the reaction device and the physical properties of the target resin, and are not particularly limited. For example, the reaction temperature is usually about 150°C to about 300°C, about 200°C to about 300°C, or about 260°C to about 300°C. In addition, the reaction pressure is usually atmospheric pressure or even about 2 Pa, and the pressure can be reduced in the later stage of the reaction.

[0064] The polymerization reaction is carried out by volatilizing diols, alkyl compounds or water to leave the reactants.

[0065] The polymerization device may be a combination of reaction groups or a connection of multiple reaction groups. In this case, the reactants are usually transferred and polymerized between the reaction groups according to the degree of polymerization. In addition, a method of equipping a horizontal reaction device in the late stage of polymerization and volatilizing while heating / mixing can also be adopted.

[0066] After the polymerization is completed, the resin is released from the reaction tank or horizontal reaction device in a molten state, and is obtained in the form of flakes that are cooled and crushed by a cooling drum or a cooling belt, or in the form of belites that are cut after being extruded in a rope form by an introduction extruder. Solid phase polymerization can also be carried out as needed to increase the molecular weight or reduce low molecular weight components. As low molecular weight components that may be contained in PET resins, such as cyclic three beam components, the content of such cyclic three beam components in the resin is usually controlled to be below 5000ppm or below 3000ppm.

[0067] The molecular weight of PET-based resins is generally in the range of 0 to 1 dL / g, 0 to 10 dL / g or 0 to 0 dL / g when expressed as the limiting viscosity measured at 30°C when the resin is dissolved in a mixed solvent of phenol / tetrachloroethane = 50 / 50 (weight ratio).

[0068] In addition, the PET resin may contain additives as required, such as lubricants, anti-blocking agents, heat stabilizers, antioxidants, antistatic agents, light-resistant agents, and impact-resistant improvers. The amount of additives added is preferably within a range that does not adversely affect the optical properties.

[0069] PET resin is usually used as a belite shape for assembly by an extruder for the preparation of these additives and the film molding described later. The size and shape of the belite are not particularly limited, but usually the height and diameter are all cylindrical, concrete or flat concrete with a height of less than 5 mm. The PET resin obtained in this way can be used as a transparent, homogeneous, and mechanically strong PET film through film forming and stretching treatment. As for its manufacturing method, it is not particularly limited, but the method described below is adopted.

[0070] The dried PET resin composition of Belite is provided to a melt extrusion device and heated to above the melting point to melt it. Then, the molten resin is extruded from the die and quenched and solidified on a rotating cooling drum to a temperature below the glass transition temperature to obtain a substantially amorphous unstretched film. This melt temperature is determined according to the melting point of the PET resin used or the extruder, and is not particularly limited, but is usually 250°C to 350°C. In addition, in order to improve the planarity of the film, it is advisable to improve the adhesion of the film to the rotating cooling drum, and it is advisable to adopt a positive transfer lamination method or a liquid coating lamination method. The so-called electrostatic recognition lamination method is usually a method of providing a linear electrode on the opposite side of the film in a direction orthogonal to the flow of the film, and providing an electrostatic charge to the film by recognizing a DC voltage of about 5 to 10 kV on the electrode to improve the adhesion of the rotating cooling drum to the film. In addition, the liquid coating lamination method refers to a method of uniformly applying a liquid to all or part of the surface of the rotating cooling drum (such as only the part in contact with the two ends of the film) to improve the adhesion of the rotating cooling drum to the film. As needed, both can also be used simultaneously. The PET resin used may be mixed with two or more resins or resins with different structures or compositions as required, for example, Belite with a granular filler, an ultraviolet absorber or an anti-blocking agent for electrification and Belite without a proportion may be mixed.

[0071] In addition, the number of layers of the extruded film can be more than two layers as required. For example, Belite prepared with a granular filler of an anti-blocking agent and Belite without a filler are prepared, and the same die is supplied from different extruders to extrude a film consisting of two or three layers of "filler preparation / no preparation / filler preparation".

[0072] The unstretched film is usually and preferentially stretched longitudinally in the extrusion direction at a temperature above the glass transition temperature. The continuous temperature is usually 70°C to 150°C, 80°C to 130°C or 90°C to 120°C. In addition, the continuous stretching ratio is usually 1 to 6 times or 2 to 5 times. The continuous stretching can be completed at one time or in multiple times as needed.

[0073] The longitudinal soft film thus obtained may be subjected to heat treatment thereafter. Then, a relaxation treatment may be performed as required. The heat treatment temperature is generally 150°C to 250°C, 180°C to 245°C, or 200°C to 230°C. In addition, the heat treatment time is generally 1 to 600 seconds, 1 to 300 seconds, or 1 to 60 seconds.

[0074] The temperature of the relaxation treatment is usually 90 to 200° C. or 120 to 180° C. In addition, the relaxation amount is usually 0.1% to 20% or 2% to 5%. The temperature and relaxation amount of the relaxation treatment can be set so that the thermal shrinkage rate of the PET film after the relaxation treatment at 150° C. is less than 2%.

[0075] When obtaining uniaxially stretched and off-axis stretched films, they are usually stretched transversely by Tent after longitudinal stretching, or after heat treatment or relaxation treatment as needed. This delay temperature is usually 70°C to 150°C, 80°C to 130°C or 90°C to 120°C. In addition, the stretching ratio is usually 1 to 6 times or 2 to 5 times. After this, heat treatment can be carried out and relaxation treatment can be carried out as needed. The heat treatment temperature is usually 150°C to 250°C, 180°C to 245°C, 200°C to 230°C. The heat treatment time is usually 1 to 600 seconds, 1 to 300 seconds or 1 to 60 seconds.

[0076] The temperature of the relaxation treatment is usually 100 to 230° C., 110 to 210° C. or 120 to 180° C. In addition, the relaxation amount is usually 1-20%, 1-10% or 2-5%. The temperature and relaxation amount of the relaxation treatment can be set so that the thermal shrinkage rate of the PET film after the relaxation treatment at 150° C. is less than 2%.

[0077] In the uniaxial stretching and off-axis stretching treatment, in order to alleviate the deformation of the back-axis after lateral stretching, such as Boeing, heat treatment or stretching treatment can be performed again. Boeing's maximum deformation in the direction of stretching away from the main axis is usually within 45 degrees, within 30 degrees or within 15 degrees. In addition, the stretching direction here refers to the general stretching direction in the longitudinal stretching or lateral stretching.

[0078] In the off-axis stretching of PET film, the transverse stretching ratio is usually slightly larger than the longitudinal stretching ratio. In this case, the stretching direction refers to the perpendicular direction relative to the long direction of the film. In addition, in the uniaxial continuous stretching, it is usually the transverse continuous stretching as mentioned above. In this case, the continuous stretching direction refers to the perpendicular direction to the same long direction.

[0079] In addition, the back-to-main axis refers to the back-to-main direction of the molecules at any point on the Lianxin PET film. In addition, the deformation of the back-to-main axis to the extension direction refers to the angle difference between the back-to-main axis and the extension direction. In addition, its maximum value refers to the maximum value in the vertical direction to the length direction.

[0080] The confirmation direction of the above-mentioned alignment main axis is a conventional technique, and for example, it can be measured using an optical material inspection device RETS (manufactured by Oijagudden Cabusicy Guisha) or a molecular backscatter meter MOA (manufactured by Oijagudden Sabusicy Guisha).

[0081] In the above-mentioned stretchable PET film, functional layers other than the above-mentioned display layer can be laminated on one side or both sides without hindering the effect of the present application. The laminated functional layers include a challenge layer, a hard coating layer, a smooth layer, a second activation layer, an anti-convolution layer and a second bonding layer.

[0082] The above manufacturing method is an exemplary method for obtaining the optical coating 7 of the present invention.

[0083] Embodiment five:

[0084] In this embodiment, based on the third and fourth embodiments, a protective film 5 is pasted on the upper surface of the optical coating 7 and the bottom surface of the anti-fog layer 4. The protective film 5 is made of silicone material and can protect both sides of the lens to play a role in transportation protection.

[0085] Experimental example:

[0086] Taking a lens made of two layers of multi-color-changing base layers 1 as an example, based on the lenses prepared in Example 1 to Example 5, one layer of the color-changing base layer 1 is red when powered on, and the other layer of the color-changing base layer 1 is blue when powered on, the light transmittance of the lens is tested using a light transmittance detector, and the test results are shown in Table 1;

[0087] Table 1

[0088] Status Steps Light transmittance Opening status State 1 58% Red Blue Off State 2 40% Red on, blue off State 3 25.50% Blue on, red off State 4 18% Both red and blue are on

[0089] Based on Table 1, the present invention can effectively perform color-changing and shading operations. The anti-fog liquid crystal lens with color-changing and shading functions can be applied in the following fields: lenses for glasses, sunglasses, ski goggles, cycling glasses, motorcycle and electric bicycle helmets, etc.; mobile devices, it can also be used for virtual reality (VR: Virtual Reality) devices, augmented reality (AR: Augmented Reality) devices, wearable devices, such as vehicle windows, building windows, etc., and can also be used in devices for outdoor applications.

Claims

1. An anti-fog liquid crystal lens with color-changing and light-shielding function, characterized in that: The invention comprises a color-changing base layer (1), wherein the color-changing base layer (1) is composed of two layers of lens substrates (11) and a dye liquid crystal color-changing layer (12) located between the two layers of lens substrates (11); a conductive layer (13) is provided on a side of the lens substrate (11) close to the dye liquid crystal color-changing layer (12); a first adhesive (3) is provided on the upper surface and the bottom surface of the color-changing base layer (1); a hardening layer (6) is provided on the first adhesive (3) located on the upper layer; an optical coating (7) is provided on the upper surface of the hardening layer (6); an anti-fog layer (4) is provided on the bottom surface of the first adhesive (3) located on the lower layer; a protective film (5) is provided on the bottom surface of the anti-fog layer (4) and the upper surface of the optical coating (7); and an FPCB control circuit (9) for controlling the change of the dye liquid crystal color-changing layer (12) through the conductive layer (13) is installed on the outer wall of the lens substrate (11) located on the upper layer.

2. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 1, characterized in that: The number of the color-changing base layer (1) is one or more layers. When the color-changing base layer (1) is multiple layers, two layers of first adhesive (3) are respectively arranged on the two end surfaces of the multiple-layer color-changing base layer (1), and a second adhesive (8) is arranged between adjacent color-changing base layers (1), and the colors of the dye liquid crystal color-changing layers (12) in the multiple-layer color-changing base layer (1) are all different.

3. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 2, characterized in that: The material of the first adhesive (3) and the second adhesive (8) is preferably OCA optical adhesive.

4. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 1, characterized in that: The material of the hardened layer (6) is preferably TAC or PC.

5. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 1, characterized in that: The material of the anti-fog layer (4) is preferably CAP or TAC.

6. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 1, characterized in that: The material of the lens substrate (11) is preferably PC or PET.

7. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 1, characterized in that: A sealing line (2) is provided at the edge between the two layers of lens substrate (11), and the sealing line (2) is used to seal the dye liquid crystal color-changing layer (12) between the two layers of lens substrate (11).

8. The anti-fog liquid crystal lens with color-changing and light-shielding function according to claim 7, characterized in that: The sealing line (2) comprises an inner sealing line (22) and an outer sealing line (21), and the dye liquid crystal color-changing layer (12) is located in the area divided by the inner sealing line (22).

Citation Information

Patent Citations

  • Lens, AR glasses and AR system

    CN114063303A

  • Liquid crystal sunglasses with dye liquid crystals

    CN203535321U

  • Variable optical attenuation eyes wearing part with colour reinforcing

    CN207704150U

  • Pair of intelligent liquid crystal dimming color-changing swimming goggles

    CN212090775U

  • Novel anti-fog lens

    CN212808828U